EXPERIENCE IN APPLICATION OF CANAKINUMAB IN PATIENTS WITH CRYOPYRIN-ASSOCIATED SYNDROME (SYNDROME CINCA/NOMID) - T. V. Sleptsova; E. I. Alexeeva; K. V. Savost'yanov; A. A. Pushkov; A. G. Nikitin; T. M. Bzarova; S. I. Valieva; A. N. Fetisova; A. V. Pakhomov; N. V. Zhurkova; R. V. Denisova; K. B. Isaeva; et al. ("Paediatrician" Publishers LLC, 2014)
The article describes the monitoring of severe cryopyrin-associated syndrome (syndrome CINCA/NOMID). The following clinical case indicates successful application of homogeneous antibodies to interleukin 1 - canakinumab - in patient with chronic neurologic dermatic articular syndrome. Fever, rush and pain syndrome completely jugulated, contractures of articulation joints decreased in a week since the beginning of the treatment. In 8 weeks of therapy movements of affected joints almost completely restored, the boy could stay, spell simple words; decreased and normalized laboratory test values of disease activity (erythrocyte sedimentation rate, C-reactive protein). In 12 weeks the child could move with assistance, say simple phrases. The following clinical case shows high efficiency of application of canakinumab in chronic neurologic dermatic articular syndrome treatment and indicates the perspectives of therapeutic use of interleukin 1 blocking agent in patients with early stage of disease before the progress of nonreversible osteohondrous destruction and serious injury of cerebrospinal nervous system. No adverse event were registered on treatment with application of canakinumab.Key words: children, autophologistic syndromes, cryopyrin-associated syndrome, CINCA/NOMID, canakinumab.